BRAND ACTIVATION AS THE EXTENSION OF MARKETING EVENT - Wijaya, Bambang Sukma (Journal Communication Spectrum : Capturing New Perspectives in Communication, 2014)
Brand activation strategy is currently a vehicle for many brands to get closer to consumers. Long before this phenomenon appeared, marketers were familiar with BTL or Below the Line as a complement to ATL or Above the Line activities, dominated by advertising in mainstream media. Then, creativity emerged by using events as a marketing tool. Why is the marketing event identified with brand activation? Why do brands need to be activated? What is activated? How to activate? This article examines the metamorphosis of the concept of brand activation. It explains how to implement an integrated brand activation (IBA) strategy, the types and spectrum of brand activation, as well as design, to turn on creativity so that brands are always active in consumers' minds using the T5 Strategy: Touch, Tease, Trap, Turn On, Tail and M-Triangle Capital: Message, Moment, Money. AKTIVASI MEREK SEBAGAI EKSTENSI AJANG PEMASARANStrategi brand activation atau aktivasi merek saat ini menjadi senjata andalan banyak merek untuk mendekatkan diri dengan konsumen. Padahal, jauh sebelum fenomena ini muncul, para pemasar mengenal istilah BTL atau Below the Line sebagai pelengkap kegiatan ATL atau Above the Line yang didominasi periklanan di media-media arus utama. Kemudian, kreativitas muncul dengan memanfaatkan event sebagai alat pemasaran. Lalu mengapa marketing event atau ajang pemasaran diidentikkan dengan aktivasi merek? Mengapa merek perlu diaktifkan? Apanya yang diaktifkan? (Message, Meaning, Reality, Sensation). Bagaimana mengaktifkan? Artikel ini mengkaji metamorphosis konsep aktivasi merek dan menjelaskan bagaimana strategi aktivasi merek yang komprehensif dapat dijalankan, jenis dan spektrum aktivasi merek, serta strategi menghidupkan kreativitas agar merek selalu aktif selamanya di benak konsumen dengan menggunakan T5 Strategy: Touch, Tease, Trap, Turn On, and Tail dan M-Triangle Capital: Message, Moment, Money. To cite this article (7th APA Style): Wijaya, B. S. (2014). Brand Activation as the Extension of Marketing Event. Journal Communication Spectrum: Capturing New Perspectives in Communication, 4(1), 13-23